The Impact of Market Segmentation on the Sales Performance of Brand Fashion Threvé - Ely Suhayati Suhayati; Maitsaa Azzahra Azzahra (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
This study aims to examine the influence of market segmentation on sales performance at Threvé, a local fashion brand, within the context of offline marketing across different locations. The central issue addressed is the variation in sales performance despite relatively consistent products, pricing, and brand identity. A case study approach was employed using qualitative analysis based on the company’s internal sales data. The analysis focused on identifying responsive market segments through sales patterns observed across various offline marketing locations. The findings reveal that differences in sales performance are largely shaped by the alignment between market segment characteristics and the marketing location context. Market segmentation based on actual consumer behavior provides a more contextual understanding than generalized segmentation approaches. These results indicate that sales performance data can serve as an effective basis for market segmentation in marketing decision-making. This study contributes conceptually to the development of behavior-based market segmentation using operational data and offers practical insights for managing marketing strategies in local fashion brands with limited resources. Keywords: Marketing Management; Market Segmentation; Sales Performance; Offline Marketing; Local Fashion Brand